Clip Thinking in Adolescence (Actual Problems of Psychology in Educational Institutions, 2019)
The main reasons of the development of clip thinking inadolescence are described in this article. Main criteria of assessment of clipthinking are defined. The examples of researching of this notion by differentscientists are given. The level of critical thinking in adolescence is analyzed andits positive and negative manifestations and their influence on the academicperformance of teens are defined. The importance of the integrated study ofthinking and life of a teenager for making right conclusions about the level ofclip thinking and its influence on life and academic performance in adolescenceis emphasized. The need for timely intervention of adults (parents, teachers) foravoiding the progress of clip thinking among teenagers.
Keywords: c lip thinking, adolescence, consequences of clip thinking, criteria of assessment, level of academic performance